Kalpana Bardhan (comp. y trad.). Of women, outcastes, peasants, and Rebels. A selection of Bengali short stories. Berkeley y Los Ángeles: University of California Press, Oxford, 1990. 330. - Devalle, Susana B. C. (Estudios de Asia y África, 1997)
-